(untitled) (UNED Research Journal, 2020)
Introduction: Teleworking is a relatively new labor modality in Costa Rica; however, sedentary lifestyle and mealtime disorders may lead to obesity and cardiovascular disease in teleworkers. Objective: To measure if teleworkers have different levels of physical activity and meal times than their counterparts. Methods: We surveyed online 241 teleworkers and 223 presential workers. Results: Presential workers reported more physical activity and better compliance with meal times. Conclusion: Teleworkers in this institution need to change activity and eating practices to reduce the danger of obesity and cardiovascular diseases.